Towards sustainable fisheries of the Öresund cod (Gadus morhua) through sub-stock-specific assessment and management recommendations - Lindegren, Martin; Waldo, Staffan; Nilsson, P. Anders; Svedäng, Henrik; Persson, Anders (ICES Journal of Marine Science, 2013)
Abstract Lindegren, M., Waldo, S., Nilsson, P. A., Svedäng, H., and Persson, A. 2013. Towards sustainable fisheries of the Öresund cod (Gadus morhua) through sub-stock-specific assessment and management recommendations. – ICES Journal of Marine Science, 70: 1140–1150. Fisheries management traditionally relies on stock assessments assuming discrete populations within large administrational areas. However, failing to account for sub-stock structuring may result in overestimation of the stocks' true harvest potential and unsustainable exploitation of small stock elements. Atlantic cod (Gadus morhua) frequently occurs in spatially segregated populations, some of which exhibit fine-scaled stock structuring within current management boundaries. Here we use the locally spawning cod stock in the Sound (“Öresund”) as a case study, and perform a sub-stock-specific assessment to evaluate biological and economic effects of managing the Sound cod as a separate stock. Our results indicate that reducing exploitation pressure, particularly through technical regulations i.e. increasing gill-net mesh sizes, would not only enhance the stock age distribution, but yield long-term net benefits to the local gill-net fishery. Furthermore, our study emphasizes the need for developing sub-stock-specific management recommendations in order to ensure the maintenance of fisheries resources in general, and the persistence of sub-stock structuring in particular.